Nutritional status among boys and girls of a central Indian Town (Sagar) - Thakur, Rachna; Gautam, Rajesh K. (Anthropological Review, 2015)
The prevalence of undernutrition is a significant area of concern in many developing countries, where it is a major public health problem. The aim of the study was to assess the prevalence of undernutrition among school-going boys and girls of central Indian city Sagar, MP. A total of 612 individuals (312 girls and 300 boys) aged 5–18 years were examined and compared to the NCHS reference data. The nutritional status was assessed using following anthropometric indicators: body height and weight, body mass index (BMI) and composite index of anthropometric failure (CIAF). It was found that girls were heavier (1 kg) and taller (2–5 cm) than boys up to 15 and 13 years of age, respectively. After that, boys became taller with 1 to 13 cm. The mean BMI of boys was higher to girls up to 10 year of age after that the trend was reversed. Comparison of the present findings with NCHS reference data revealed that Indian girls and boys were lagging behind. The difference in body weight between the reference data and the present sample was around 5 to 6 kg. The pattern of difference in body height revealed small amount during early childhood (6.6.cm and 9.6 cm in girls and boys 5 years of age). This difference more than doubled at the age of 14 years in girls 16.7 cm and in boys 17.5 cm (p<0.01). Similar pattern was found for BMI with 6.5 kg/m2 and 6.3 kg/m2 in 14 years old girls and 16 years old boys (p<0.01). Z-score values of weight-for-age, height-for-age and BMI-for-age revealed that that boys were more likely to be stunted than girls whereas girls were more likely to be underweight and undernourished than boys. In terms of CIAF 10.6% girls and 10% boys were undernourished. The results of the present study indicate that there is great need for implementation of health programmes to eliminate gender inequalities and improve children’s health.